High-risk sexual behaviors while on depot medroxyprogesterone acetate as compared to oral contraception. Issue 1 (December 2017) - Bartz, Deborah; Maurer, Rie; Kremen, Jessica; Fortin, Jennifer; Janiak, Elizabeth; Goldberg, Alisa
Abstract Background Depot medroxyprogesterone acetate (DMPA) contraceptive use is associated with an increased risk forChlamydia infection. However, prior studies inadequately account for potential differences in sexual behavior between users of DMPA and users of other contraceptive methods. In this study we compare sexual risk-taking behavior in women using DMPA to women using oral contraceptive pills (OCP) to assess risk ofChlamydia trachomatis infection. Methods In this cross-sectional study of 630 reproductive-aged women seeking routine gynecologic care (449 OCP and 181 DMPA users) sexual risk-taking was evaluated by use of the Safe Sex Behavior Questionnaire, a validated measure of sexual behaviors and attitudes. All women were screened forChlamydia . Logistic regression estimated the association of contraceptive choice, sexual behaviors, andChlamydia infection. Results Oral contraceptive pill users differed from DMPA users in age, race, marital status, education level, and pregnancy history (p -values all <0.05). Oral contraceptive pill users had used their method of contraception for longer average duration (p  < 0.01) and reported greater frequency of condom use (p  < 0.01). Eleven (2.5%) OCP and 2 (1.1%) DMPA users hadChlamydia (p  = NS). Conclusions Oral contraceptive pill and DMPA users differed with respect to both demographic factors and frequency of condom use. Odds of currentChlamydia infection did not differ between OCP and DMPA users when controlling for sexual risk-taking or demographic factors, though due to lowChlamydia rates in our population, this study was underpowered to detect this difference.